Penerapan Metode Value Engineering Untuk Optimalisasi Biaya Pada Proyek Lanjutan Pembangunan Gedung Plut Pasuruan - Deni Agustin; Asnun Parwanti; Saiful Arfaah (GLOBAL SCIENTS PUBLISHER, 2025)
The construction of the Integrated Business Service Center for Cooperatives and micro small and medium enterprises in Pasuruan City is a strategic step by the government in supporting micro small and medium enterprises. However, the project was halted for five years due to a corruption case, causing the building to be abandoned and causing state budget losses. From this background, The application of the Value Engineering method can help identify alternative architectural and material work in the continuation project of the PLUT Building construction and cost savings that can be achieved through the application of the Value Engineering method in the project.. The objectives of the research are to analyze the application of the Value Engineering method in determining alternative work and more economical material replacement without reducing the function and quality of the project, and Calculating the potential cost savings that can be obtained through the application of the Value Engineering method in the continuation project of the PLUT Building construction. The research used is empirical juridical using secondary data analysis such as the Cost Budget Plan and Work Unit Price Analysis. The analysis was carried out through systematic stages of Value Engineering, starting from the information stage (Pareto analysis and Breakdown Cost Model), creative stage, analysis, to the cost comparison recommendation stage. The results of this study indicate that the abandonment of the project from 2018 to 2025 resulted in cost escalation due to inflation of Rp 321,067,459 and asset depreciation of Rp 219,581,300. The application of Value Engineering resulted in more efficient material alternatives, such as the use of 3” aluminum frames and gypsum boards for ceilings. This recommendation succeeded in reducing the cost of architectural work to Rp. 622,155,307.53. Savings of Rp. 4,647,795.87 or 0.74% proves that Value Engineering can provide efficient technical solutions and is feasible to be applied to government construction projects.